2021
DOI: 10.1002/1348-9585.12296
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment to inhalable and respirable dust in the post — earthquake construction sites in the city of l’Aquila

Abstract: Objectives Following an earthquake that occurred in middle Italy in 2009, the involved territory hosted in 10 years thousands of construction sites. The aim of this study is to assess inhalable, respirable, and respirable crystalline silica exposure of the construction workers involved in the rebuilding activities. Methods Six construction companies joined the study and hosted the air sampling activities. We identified four work tasks: bricklayer and similar; scaffolder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…As shown in Table 2, perception of workers was, on average, low. This perception contradicts the findings reported in the scientific literature (13,22,23). Our interviewees assigned the highest mean value to physical risks exposure and the lowest to biological risks.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2, perception of workers was, on average, low. This perception contradicts the findings reported in the scientific literature (13,22,23). Our interviewees assigned the highest mean value to physical risks exposure and the lowest to biological risks.…”
Section: Discussioncontrasting
confidence: 99%
“…The construction industry is one of the most dangerous businesses for the safety and health of workers. Indeed, construction workers suffer from many work-related illnesses and are subject to workrelated injuries (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“… 14 Following an earthquake in central Italy in 2009, the affected region witnessed thousands of construction sites over the course of 10 years. Mastrantonio et al 20 determined that workers engaged in manual demolition activities were exposed to inhalable dust particles exceeding the threshold limit value of 10 mg/m 3 .…”
Section: Inhaled Irritants and Respiratory Impactsmentioning
confidence: 99%
“…Similarly, a study by Mannetje et al ( 19 ) reported a decline in dust exposure over time for a pooled analysis of studies conducted from different parts of the world. In the construction industry, Mastrantonio et al ( 15 ) assessed inhalable, respirable, and respirable crystalline silica dust exposure among construction workers (bricklayers, scaffolders and carpenters) in rebuilding activities. The results revealed that geometric means for inhalable dust, respirable dust and respirable crystalline silica were 4.3 mg/m 3 , 0.25 mg/m 3 and 0.004 mg/m 3 , respectively, which implied that all jobs were below the ACGIH TLV of 3 mg/m 3 for dust and 0.025 mg/m 3 for crystalline silica.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies indicating that respirable dust exposure can cause occupational respiratory diseases have been conducted and they highlight specific jobs in the mining industry where workers may be highly exposed to respirable dust and respirable crystalline silica dust (13)(14)(15). All mine workers are potentially at risk of exposure to respirable dust in surface or underground operations.…”
Section: Introductionmentioning
confidence: 99%